A new ladder-type dichloro(2, 2-dimethyl-1, 3-diaminopropane) copper complex: Synthesis, structural studies and selective sensing behavior towards a ketone molecule. (15th September 2019) - Azam, Mohammad; Al-Resayes, Saud I.; Alam, Mahboob; Trzesowska-Kruszynska, Agata; Kruszynski, Rafal; Siddiqui, Mohammed Rafiq H.
Graphical abstract: A new ladder-type dichloro(2, 2-dimethyl-1, 3-diaminopropane) copper complex has been investigated. The experimental findings were confirmed by DFT calculations. In addition, the sensing behavior of the studied complex towards a ketone was explored. Abstract: A new coordination compound with the formula [Cu(dmpd)Cl2 ], where dmpd stands for 2, 2-dimethylpropane-1, 3-diamine, was prepared and structurally characterised by elemental analyses, IR and UV/Vis spectroscopic studies. The single crystal X-ray crystallographic study revealed the copper cation to be six coordinated in the complex by two amine nitrogen atoms and four chloride ions. The copper atom adopts a distorted tetragonal bipyramidal geometry, with two bridging chloride ions located at the polyhedron apexes. Furthermore, to obtain insight into the structure, theoretical studies were performed. The complex exhibits a strong photoluminescence property in tetrahydrofuran and shows a strong sensing behaviour towards a ketone molecule, proving it to be a good candidate for sensing measurements.